2006
DOI: 10.1007/s10143-006-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological features related to the growth potential of meningioma

Abstract: Clinical and radiological features that help predict the growth potential of meningioma would be beneficial. The purpose of this study is to clarify the characteristics related to proliferating potential using the MIB-1 staining index. We analyzed the relationship of MIB-1 staining indices to characteristics of 342 consecutive patients with meningioma surgically removed between 1995 and 2004 by logistic regression analysis. One hundred and forty-nine of the patients with meningioma were ≥60 in age; 89 male; 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
73
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 20 publications
13
73
2
3
Order By: Relevance
“…Other studies have reported that hyperintensity on T2-weighted imaging, a non-skull base location and the absence of calcification on imaging are considered positive indicators of tumor growth in intracranial meningiomas (30,31). In addition, a non-skull base location and the absence of calcification correlate with a high tumor proliferation index (MIB-1) in intracranial meningiomas (32)(33)(34)(35). To determine the MIB-1 staining index, the number of cells stained positively with MIB-1 and the total number of cells were counted in several representative fields containing >1,000 cells, and the ratio was defined as the MIB-1 staining index.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that hyperintensity on T2-weighted imaging, a non-skull base location and the absence of calcification on imaging are considered positive indicators of tumor growth in intracranial meningiomas (30,31). In addition, a non-skull base location and the absence of calcification correlate with a high tumor proliferation index (MIB-1) in intracranial meningiomas (32)(33)(34)(35). To determine the MIB-1 staining index, the number of cells stained positively with MIB-1 and the total number of cells were counted in several representative fields containing >1,000 cells, and the ratio was defined as the MIB-1 staining index.…”
Section: Discussionmentioning
confidence: 99%
“…Some remain unaltered in size for a long period, while others tend to grow fast (10). Surgical resection remains the treatment mainstay (1,24).…”
Section: Discussionmentioning
confidence: 99%
“…Kasuya et al 10 reported that male gender was an independent risk factor for high proliferative potential. The mean Ki-67 LI and p63 with respect to age and gender was not statistically significant in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Most meningiomas occur in adults between the ages of 20 to 60 years, with a peak incidence around 4 th decade of life. 1 Meningiomas most likely occur in women with ratio of female to male 2:1 intracranially and 1:10 intraspinally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation